Healthcare resource utilization among commercially insured patients with cold agglutinin disease in the United States. (2nd August 2020) - Su, Jun; Bylsma, Lauren C.; Jiang, Xiaohui; Morales Arias, Jaime; Jain, Nisha; Nordyke, Robert J.
Abstract: Aims: Cold agglutinin disease (CAD) is a rare subtype of autoimmune hemolytic anemia associated with increased thromboembolism risk and early mortality. Healthcare resource utilization (HRU) in CAD has not been reported. We aimed to compare HRU of patients with CAD with a matched non-CAD cohort in the United States. Materials and methods: Patients with CAD were identified from 2006 to 2016 in the Optum-Humedica database using CAD terms in clinical notes and hematologist review. Patients were required to have Integrated Delivery Network records and ≥6 months' follow-up before and after the first CAD mention date (index date). Patients with CAD were matched to a non-CAD cohort based on demographics. Multivariate analyses assessed inpatient hospitalizations, outpatient visits, emergency room visits, and transfusion use between cohorts 6 months before and 12 months after the index date. Results: Of 814 patients with CAD, 410 met inclusion criteria and were matched to 3, 390 patients without CAD. Mean age of patients with CAD was 68.0 years; approximately 62% were female. In the 12 months after the index date, mean inpatient hospitalizations (0.83 vs. 0.25), outpatient visits (17.26 vs. 6.77), emergency room visits (0.55 vs. 0.32), and transfusion days (1.05 vs. 0.05) were higher for patients with CAD than the matched non-CAD cohort (all p < .0001). Similarly, in the 6 months before the index date, patients with CAD had higher HRU than matched patients without CAD for all measures evaluated. Limitations: Results of this study are based on patient information from the Optum-Humedica database, which is limited to commercially insured patients and may not represent the overall CAD population. Conclusions: CAD places a substantial burden on patients and healthcare systems. In addition, the high HRU for patients with CAD observed in the 6 months before diagnosis indicates that disease awareness and better diagnostic practices may be needed.